Genetic variability of the regulatory region of the FSH-β gene and its association with reproductive traits in Nellore bulls - Lorena K. Silva; Cintia L. Santos; Elizabeth M. Barbosa; Sebastiao T. Filho; Janaina B. Luz; Kaliandra S. Alves; Luis R. Oliveira; Ednaldo S. Filho (Iraqi Journal of Veterinary Sciences, 2024)
Molecular biology techniques are important tools for studying animal health and production characteristics. Thus, determining the genotypes of animals with high genetic value enables the implementation of genetic improvement programs, especially related to sperm and testicular characteristics in cattle. The objective of this study was to detect polymorphisms in the promoter region of the FSH-β gene using the Tetra-primer-PCR (T-ARMS-PCR) technique and associate these polymorphisms with seminal parameters and scrotal perimeter in Nellore bulls. Semen samples were collected and evaluated for volume, sperm motility, and vigor, and scrotal perimeter was measured in 200 bulls. DNA extractions and genotyping of the FSH-βU1 and FSH-βU2 polymorphisms were performed using the T-ARMS-PCR technique. Population genetics parameters were estimated, and associations between genotypes and semen and testicular characteristics were assessed. Both SNPs showed variability with allele frequencies close to 0.500 and an excess of heterozygotes (above 0.600). No inbreeding was detected (FIS -0.3304 and -0.2511, respectively), and deviations from Hardy-Weinberg equilibrium were observed (P<0.05). Only the scrotal perimeter parameter was associated with the FSH-βU1 SNP, with the GG genotype being superior to the others. Therefore, the T-ARMS-PCR technique may be applied to different SNPs directly associated with health and economically relevant characteristics in animals.